A Multicenter Retrospective Study of Epithelioid Trophoblastic Tumors to Identify the Outcomes, Prognostic Factors, and Therapeutic Strategies - Liu, Wu; Zhou, Jianwei; Yang, Jie; Huang, Xiufeng (Frontiers in Oncology, 2022)
Background: There was no consensus for management of Epithelioid Trophoblastic Tumor (ETT) up to date. Objective: ETT is the rarest form of Gestational Trophoblastic Neplasia (GTN). Our goal was to assess the outcomes and explore the prognostic factors of patients with ETT through this multicenter retrospective analysis and devise a risk-adapted approach to clinical management. Methods: 31 patients were validated as ETT pathologically between January 2004 and June 2021 from three tertiary hospitals. We retrospectively analyzed the characteristics, treatments, outcomes and prognostic factors. Results: 8 patients experienced a recurrence and 6 patients died of ETT resulting in a mortality rate of 19.4%. 5 patients with stage I had fertility preserving treatment. Of whom, one patient had a full-term delivery, whereas a 23-year-old patient who declined hysterectomy died of recurrent disease. 8 patients of extrauterine ETT with isolated pulmonary lesion had a younger age at diagnosis (median 30.5 VS 41, p=0.003) and a smaller tumor size (median 2.4 vs 4.8cm, p=0.003) compared to other patients with metastatic disease and none of them died. Multivariate analyses showed number of metastases ≥3 (HR 28.16, p=0.003) was the only significant predictor associated with adverse overall survival, while number of metastases ≥3 (HR 9.59, p=0.005) and chemotherapy alone (HR 16.42, p=0.001) were associated with adverse recurrence-free survival. Patients in stage I or with number of metastases <3 had a favorable prognosis, whereas the prognosis of patients with number of metastases ≥3 remains poor. Conclusions: Chemotherapy alone is insufficient for patients with ETT. Surgical procedures are the mainstay of management for ETT patients. Combined surgery and multi-agent chemotherapy are recommended for patients with metastatic disease and localized disease with persistently positive hCG levels after surgery. Number of metastases ≥3 is the most critical risk factor for ETT.